An empirical analysis on the effects of tertiary level educational attainment on poverty in the Philippines, 1990-2018 - Sodsod, Bryan Dave S.; Flores, Riz Mart V.; Belchez, Denmark; Medina, Rafael T. 4 0 16; 5
ABSTRACT: Education and poverty are closely linked together. There is clear empirical evidence that proves how education affects the poverty rate. In Human Capital Theory, education is used as the main indicator that greatly contributes to the productiveness and efficiency of an economy. This econometric study provides empirical analysis on the effect of Higher Education to the poverty rate in the Philippine context. With the sources from Philippine Statistics Authority and World bank, the study aims to provide empirical observation to justify the rate of poverty align with the increasing number of college degree holders. This study also includes a multiple regression process to assess the effect of unemployment rate and population growth which is also a huge contributor and indicator of economic performances. Statistical results show how poverty behave to an increasing number of college graduates, unemployment rate and population growth in and only in the Philip
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2